Pengaruh Lingkungan Kerja, Kompensasi Finansial Dan Kompensasi Non Finansial Terhadap Kepuasan Karyawan Pada Perusahaan Mikro Hamdi Jaya Kabupaten Pasuruan - Aniyah, Nabila Masrurotul; Djaelani, Abdul Kodir; Dianawati, Eris (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The results of this research aim to determine Price, Promotion and Barand Image on Maxim User Decisions in a study on FEB Students of the Islamic University of Malang Class of 2020. Based on the results of this research, it shows that the price variable has a positive and significant effect on user decisions with a significant value of 0.001<0.05, the Promotion variable has a positive and significant effect on User Decisions with a significant value of 0.028<0.005 and the Brand Image variable has a positive and significant effect on User Decisions with a significance value of 0.14<0.05. Keywords: Work Environment, Financial Compensation And Non-Financial Compensation